The Influence of Financial Ratio to Profit Growth - Vaya Juliana Dillak; T.A. Siburian (JAF (Journal of Accounting and Finance), 2021)
The purpose of this study was determining the effect of financial ratios consisting of company size,current ratio, debt to equity ratio, and total assets turnover on profit growth in Property, RealEstate and Building Construction Service Sector Companies listed on the Indonesia StockExchange in 2015-2018. Sampling technique employed in this study is purposive samplingtechnique. There have been 13 companies sampled within 4 years, in order that 52 samples wereobtained. The analysis technique utilized in this study used panel data regression analysis. Theresults of the research company size variables, current ratio, debt to equity ratio, and total assetsturnover have an impact on profit growth by 32.7%, and therefore the remaining 67.3% isinfluenced by other factors outside the research variable. Partially, the variable Company Sizeand Total Assets Turnover incorporates a significant positive effect on Profit Growth, whileCurrent Ratio and Debt to Equity Ratio don’t have any significant effect on Profit Growth